Activity Levels of Amine Transaminases Correlate with Active Site Hydrophobicity. Issue 11 (31st August 2022) - Kollipara, Manideep; Matzel, Philipp; Bornscheuer, Uwe; Höhne, Matthias
Abstract: Amine transaminases (ATAs) are biocatalysts for the synthesis of chiral amines and can be identified in sequence databases by specific sequence motifs. This study shows that the activity level towards the model substrate 1‐phenylethylamine can be predicted solely from the sequence. To demonstrate this, 15 putative ATAs with a different distribution of hydrophobic or hydrophilic amino acid side chains near the active site were characterized. Hydrophobic side chains were associated with a high activity level and were a better predictor of activity than global sequence identity to known ATAs with high or low activities. Enzyme stability investigations revealed that four out of the 15 ATAs showed a good operational stability. Abstract : Amine transaminases are attractive enzymes for the synthesis of chiral amines. Their activity level correlates with the presence of hydrophobic amino acids in the active sites. This knowledge helps to guide the selection of putative enzymes in a database search.